Norge i Latin-Amerika Forbindelser og forestillinger - Marsteintredet, Leiv (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
Despite long traditions for contact with Latin America, increasing trade and investments in the region and important contributions to the recent peace process in Colombia, Latin America is often depicted as a "forgotten region" in Norway. Through a series of thematic analyses of the extent of Norway's contacts with Latin America, the authors of this anthology seeks to correct this perceived image of a "forgotten region".